Respostas

2014-01-10T20:05:44-02:00
A ) x ² + x - 12 < 0

\boxed{A = 1 , B = 1 , C = -12}

Δ = b² -4ac
Δ = 1² - 4.1.(-12)
Δ = 1 - (-48)
Δ = 49 ------------- > √49 = 7

x = - b 
± √Δ
          2a

x = -1 ± 7
         2

x' = -1 + 7 = 6 = 3
         2       2

x" = -1 - 7 = -8 = -4
          2       2

R {  3 , -4 } 

b ) 
2x² + x - 1 > 0

\boxed {A = 2 , B = 1 , C = -1}

Δ = 1² - 4ac
Δ = 1 - 4.2.(-1)
Δ = 1 - (-8)
Δ = 9 ------------ > √9 = 3

x = - 1 
± √9
         2.2

x = - 1 
± 3 
          4

x ' = - 1 + 3  = 2 = 0,5
           4         4

x" = -1 - 3 = -4 = -1
          4        4

R = { 0,5 , -1 }